2013
DOI: 10.11646/zootaxa.3702.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Pseudonannolene Silvestri, 1895 from razilian limestone caves (Spirostreptida: seudonannolenidae): synotopy of a troglophilic and a troglobiotic species

Abstract: Pseudonannolene ambuatinga n. sp. and Pseudonannolene saguassu n. sp. are described from individuals collected in limestone caves in the municipality of Pains, Minas Gerais, Brazil, which comprises a scenario of great conflict between speleological preservation and limestone extraction. The two species differ in their gonopod morphology and in size and color. Pseudonannolene ambuatinga n. sp. is regarded as the second troglobite species known for the family. This is the first report for Brazil of syntopy in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 0 publications
0
16
0
4
Order By: Relevance
“…Although more than 11,000 caves have been documented in Brazil, this may represent only 10% of the potential number of caves in the country (Auler et al 2001). Studies performed in unexplored areas have revealed dozens of new troglobitic taxa, some of which were only recently described (Pellegrini and Ferreira 2014, Azara and Ferreira 2013, Iniesta and Ferreira 2013). One of the undescribed species, sampled in a karst area in northeastern Brazil, is a freshwater flatworm hereby assigned to the suborder Cavernicola (Platyhelminthes: Tricladida).…”
Section: Introductionmentioning
confidence: 99%
“…Although more than 11,000 caves have been documented in Brazil, this may represent only 10% of the potential number of caves in the country (Auler et al 2001). Studies performed in unexplored areas have revealed dozens of new troglobitic taxa, some of which were only recently described (Pellegrini and Ferreira 2014, Azara and Ferreira 2013, Iniesta and Ferreira 2013). One of the undescribed species, sampled in a karst area in northeastern Brazil, is a freshwater flatworm hereby assigned to the suborder Cavernicola (Platyhelminthes: Tricladida).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, from the approximately 2,000 sampled caves in Brazil, only a few hundred are inhabited by obligate cave fauna. The recent discoveries of troglobitic species in Brazil are certainly due to an improvement on the sampling efforts in many previously non-prospected areas in Brazil (Prevorčnik et al 2012, Ázara and Ferreira 2013, Fišer et al 2013, Iniesta et al 2012, Iniesta and Ferreira 2013, 2013a, 2013b, Bastos-Pereira and Ferreira 2015, Vasconcelos and Ferreira 2016.…”
Section: Global Relevance Of the Two Neotropical Hotspots Of Subterramentioning
confidence: 99%
“…Since most of the karstic areas of the world are situated in temperate regions, a higher cave biodiversity can be expected in mid-latitudes because caves have served as refugia for many ancestors of obligate cave faunas during strong climate changes in the past (Bar 1968, Romero 2009). However, the high numbers of new species recently discovered in Brazilian caves (Prevorčnik et al 2012, Ázara and Ferreira 2013, Fišer et al 2013, Iniesta et al 2012, Iniesta and Ferreira 2013, 2013a, 2013b, Bastos-Pereira and Ferreira 2015, Vasconcelos and Ferreira 2016 and their high degree of troglomorphism indicate that the events of climatic changes in the Neotropics, even if not so severe as in temperate regions, could have led to the isolation of subterranean lineages. Alternatively, other mechanisms of isolation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, other caves that are not considered of maximum relevance can be severely impacted. Currently, seven troglobitic millipedes species are known from Brazil (Schubart 1946a(Schubart , 1946b(Schubart , 1957Golovatch & Wytwer 2004;Iniesta et al 2012;Iniesta & Ferreira 2013a, 2013b. Among these, two species belong to the genus Pseudonannolene Silvestri, 1895: P. spelaea Iniesta & Ferreira 2013 from iron ore caves of Para state (Iniesta & Ferreira 2013a), and P. ambuatinga Iniesta & Ferreira 2013 from limestone caves of Minas Gerais state (Iniesta & Ferreira 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, seven troglobitic millipedes species are known from Brazil (Schubart 1946a(Schubart , 1946b(Schubart , 1957Golovatch & Wytwer 2004;Iniesta et al 2012;Iniesta & Ferreira 2013a, 2013b. Among these, two species belong to the genus Pseudonannolene Silvestri, 1895: P. spelaea Iniesta & Ferreira 2013 from iron ore caves of Para state (Iniesta & Ferreira 2013a), and P. ambuatinga Iniesta & Ferreira 2013 from limestone caves of Minas Gerais state (Iniesta & Ferreira 2013b). For these species, the strong depigmentation, a reduction of the number of ocelli and a relative decrease in body size in comparison to non-troglobitic species are recognized as troglomorphic traits (Iniesta & Ferreira 2013a).…”
Section: Introductionmentioning
confidence: 99%